Persepsi Siswa terhadap Mata Pelajaran SKI pada Kurikulum Merdeka di MAN 2 Kota Bengkulu - Endang Lestari; Iin Larasati; Lulut Triwuryani; Rini Melati Sukma; Iben Herlanda (Pusat Riset dan Inovasi Nasional, 2025)
Fun learning can make students like the subject of Islamic Cultural History (SKI). Students' perception of learning Islamic Cultural History (SKI) is a boring subject. The purpose of this study is to describe students' perceptions of Islamic Cultural History (SKI) subjects in the Merdeka curriculum at MAN 2 Bengkulu City. The method used in this study is a quantitative descriptive method. Data collection techniques through observation, questionnaires, and interviews. Data analysis techniques with average tests. The results of this study showed that 21.8% of students did not like the Islamic Cultural History (SKI) lesson due to several factors, namely: 1). Learning methods are less varied, 2). Wide material coverage, 3). Material tends to be memorized. Then 40.6% of students feel uncomfortable in learning Islamic Cultural History which is influenced by: 1). The classroom atmosphere is hot, 2). Classes that are not conducive, 3). Study during the daylight hours.